Color Difference Evaluation Model on Partly Changed Complex Images - Zi dong Zhang; Jiemin Zhang; Yongmei Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Since there has been a strong demand from industry to have an efficient way of managing color image quality presented in different media, by specifically investigating partly changed complex images, this article proposed a revision to existing CIE color difference model which cannot give a proper color difference assessment on partly changed complex images. The key method applied is to find out weight coefficients of color attributes such as lightness, hue and chroma in color difference prediction.